2017
DOI: 10.1038/s41598-017-14029-0
|View full text |Cite
|
Sign up to set email alerts
|

Soloxolone methyl inhibits influenza virus replication and reduces virus-induced lung inflammation

Abstract: Highly pathogenic influenza viruses pose a serious public health threat to humans. Although vaccines are available, new antivirals are needed to efficiently control disease progression and virus transmission due to the emergence of drug-resistant viral strains. In this study, we describe the anti-viral properties of Soloxolone methyl (SM) (methyl 2-cyano-3,12-dioxo-18βH-olean-9(11),1(2)-dien-30-oate, a chemical derivative of glycyrrhetinic acid) against the flu virus. Anti-flu efficacy studies revealed that SM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 69 publications
2
25
0
Order By: Relevance
“…Earlier, we showed that SM exhibited anti-inflammatory activity in animal models with primary local inflammation, such as influenza virus A-induced pneumonia [ 55 ], as well as carrageenan and histamine-induced paw oedema [ 73 ]. Here, the anti-inflammatory effect of SM was studied in vivo using models of LPS-induced endotoxemia and carrageenan-induced peritonitis, both of which are models of acute inflammation, but with different triggers and mechanisms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier, we showed that SM exhibited anti-inflammatory activity in animal models with primary local inflammation, such as influenza virus A-induced pneumonia [ 55 ], as well as carrageenan and histamine-induced paw oedema [ 73 ]. Here, the anti-inflammatory effect of SM was studied in vivo using models of LPS-induced endotoxemia and carrageenan-induced peritonitis, both of which are models of acute inflammation, but with different triggers and mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we showed that SM displays anti-inflammatory activity; SM caused a significant and dose-dependent decrease in NO production in LPS-activated J774 murine macrophages [ 54 ]. Moreover, we showed that SM inhibits the influenza virus A-activated expression of IL-6 and TNF-α and prevents the development of inflammatory changes in lung tissue caused by the virus in mice [ 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…The structure of TM was further confirmed by 1 H and 13 C-NMR and high-resolution mass spectrometry. Given the revealed ability of SM to suppress the inflammatory response of lipopolysaccharide (LPS)-stimulated J774 macrophages in vitro [16] and carrageenan-induced acute paw edema and influenza A-associated pneumonia in murine models [15,17], we questioned whether the formation of an additional enone moiety in rings D/E along with the enone system in ring C increased the antiinflammatory properties of the molecule in vitro and in vivo. Here, we showed that TM effectively suppressed NO production by LPS-challenged J774 macrophages in vitro and dextran sulfate sodium (DSS)-induced colitis in mice in vivo.…”
Section: Synthesis Of Tmmentioning
confidence: 99%
“…The modification of natural materials by this group was shown to significantly Previously, our research group synthesized and evaluated the bioactivities of soloxolone methyl (SM), a position isomer of bardoxolone methyl based on a 18βH-glycyrrhetinic acid scaffold [10]. We showed that SM effectively inhibited tumor cell growth in vitro [10] and in vivo [15] and displayed marked anti-inflammatory and anti-influenza A activities [15][16][17]. In our previous report, structureactivity relationship (SAR) analysis revealed that the acceptor center at C-9 in ring C was crucial for the bioactivity of SM-an analog of SM with a saturated 9(11)-double bond was found to display a significantly lower cytotoxicity and a significantly lower inhibitory effect on nitric oxide (II) (NO) production by inflamed macrophages compared to SM [16].…”
Section: Introductionmentioning
confidence: 99%
“…Lupane 2,3-secoderivatives are able to suppress the reproduction of HSV-1 and Flu A (EC 50 from 1.9 to 21.3 µM) [13]. 2-Cyano-glycyrrhetic acid exhibits Flu A H1N1 antiviral activity causing a more than 10-fold decrease in virus titer [14]. Glycyrrhizic acid conjugates with aminoacids show activity against Flu A (H3N2, H1N1, H5N1, SI ranged from 10 to 29), and HRSV (SI 25) [15].…”
mentioning
confidence: 99%